Damming Trans-boundary Rivers: A Welfare Analysis of Conflict and Cooperation - Yuyu Zeng; Harold Houba; Ariel Dinar; Miroslav Marence (Tinbergen Institute, 2016)
Dams are essential for water storage and hydropower generation, but change river flow patterns and endanger local environments. Dam projects may further exacerbate already existing problems in trans-boundary rivers. We consider three scenarios of institutional factors: (1) each country pursues its own interests, (2) efficient cooperation along the river and (3) partial cooperation among neighboring countries. We conduct cost-benefit analyses for these scenarios incorporating dam projects and their externalities. We demonstrate our approach for the Mekong River incorporating expert hydrological knowledge regarding installed hydropower capacity and dam location instead of the standard economic assumptions of such costs. Our results show that cooperation between Laos and Cambodia internalizes the negative impacts of dam construction in Laos on fishery in Cambodia, and Laos refrains from building some planned dams. Our results also hint that the 1995 Mekong agreement among Thailand, Laos, Cambodia and Vietnam is internally stable.
Keywords: C61; C70; D60; Q20; Q50; R10; 330; Trans-boundary river basin management; Institutional factors; Dams; Externalities; Welfare analysis; Conflict and cooperation